A comparative study of the economic and social functioning of Vietnamese-Australians with low English proficiency living with psychotic illness. (June 2015) - Stolk, Yvonne; Sevar, Katherine; Tran, Nga; Mancuso, Serafino G; Chopra, Prem; Castle, David
Background: Because national surveys of people living with psychotic disorders tend to exclude people with low English proficiency (LEP), little is known of their economic and social functioning. Culturally influenced explanatory models may result in delayed presentation and poorer functioning. Aims: The study aimed to compare the functioning of LEP Vietnamese-Australian and Australian-born patients with psychosis and to investigate the Vietnamese-Australians' pathways to care. Method: In all, 19 LEP Vietnamese-Australians, previously excluded from the Australian Survey of High Impact Psychosis (SHIP), were matched with 15 Australian-born controls, and interviewed by a Vietnamese bilingual mental health professional using the SHIP Interview Schedule. Results: The Vietnamese-Australian patients were significantly more likely to live with family, rate spirituality as important and participate in community rehabilitation programs. Their work, social and independent functioning, was better than the controls. The groups did not differ in mental health services received and satisfaction with services. Although half of Vietnamese-Australians attributed mental illness to supernatural, among other causes, none had consulted traditional healers. Conclusions: Despite LEP, Vietnamese-Australians with psychosis showed comparable or better functioning than Australian-born patients. Further investigation is recommended into LEP patients' clinical and social recovery and the role of language communities' support networks.